Forecasting The Demand of Jernang Extract (Daemonorops spp) in The Export Market - Dedy Fitriandi; Jangkung Handoyo Mulyo; Dwidjono Hadi Darwanto (Foresty Faculty of Hasanuddin University, 2020)
One indicator of a country’s progress is economic growth. In an economic growth, export is an important component in contributing to a positive trade and balance. Indonesia as one of the developing countries always looking for a various way to increase the number of export value. To achieve thesegoals, Indonesia started the exploitation of its forest to obtain more valuable commodities that are in demands by the global markets.One of the high-value forest plants that have the zero potential to the environment damage is the Jernang extract (Daemonorops sp)that has been used as a raw material in the manufacture of the traditional medicine in several countries, e.g. China, Taiwan, and Hong Kong. The opportunity to make Jernang extract as one of the major foreign commodities for the country’s development is relatively open. But in the current situation, the utilization of Jernang extract has not been fully used and the matter of fact that there is limited information about the world’s demand for the Jernang extract. The aim of this study isto find out the possibility of the needs of Jernang extract in the future. All the data regarding the Jernang extract will be processed using the methodology of Single Exponential Smoothing Techniques. The result of this studyshows that the demand of jernang was fluctuated but still in the trend of large demand. This study recommends that the government need toencourage people to develop Jernang plantation.